Stability-indicating determination of ciprofloxacin in the presence of its main photo-degradation product using solid-contact electrodes in river water - Sherif A. Abdel-Gawad (Journal of Applied Pharmaceutical Science, 2024)
The application of membrane sensors for monitoring and evaluation of pharmaceutical environmental contaminants has become a significant aim in the past few years. Due to the wide applicability of ciprofloxacin hydrochloride (CPF) in medicine, there is a high probability of its presence in the environment, especially in surface water like river water. The long-term exposure of the river water to sunlight and the photoliability of CPF may increase its photo-degradation. Two selective and sensitive membrane electrodes were created to measure CPF when it is present with its main photo-degradant product. These were made using two ion pairing agents, which are sodium tetraphenylborate (TPB) and phosphotungstic acid (PTA). The linearity range of the manufactured electrodes was 1 × 10-6–1 × 10-2 M. The slopes of the CPF-TPB and CPF-PTA membrane electrodes are 60.1 ± 0.70 and 57.9 ± 0.90 mV/decade, respectively. The cited sensors showed adequate performance in a pH range from 2.0 to 5.0. All test parameters were fine-tuned to provide the best electrochemical performance. The manufactured membranes were successfully used to determine CPF in a sensitive way in the presence of its primary photodegradant. The cited sensors were effectively used to quantify CPF in river water samples, with no pre-treatment operations required.
Keywords: Sensors, ciprofloxacin hydrochloride, ion-selective membranes, phosphotungstic acid, sodium tetraphenylborate, river water samples